Tentativas de suicídio e suicídios em profissionais de segurança pública do Estado do Ceará: magnitude, perfil e fatores associados - Sousa, José Edir Paixao de Sousa (2016)
The objective of this study was to characterize the magnitude, profile and potential factors associated with suicide and suicide attempts, practiced by public security professionals from the State of Ceará. The research method was to identify the cases of suicides of these professionals from the State of Ceará between 2000 and 2014 (fifteen years) and to elaborate a historical series, to calculate the suicide rates, the potential years of life lost and to describe the distribution of frequency. For the suicide attempts, the period was from 2010 to 2014 (five years), in addition to the survey of attempts of these professionals in a series of cases, there was the description of frequency distribution, calculation of trial rates and statistical associations for multiple Cases and cases (suicides). The results of the survey indicated n = 57 suicides in the period studied, a suicide rate in public security professionals (per 100 thousand), standardized by males and the adult age of 23.9 while the standardized rate of the population of Ceará, also for the Males and adults was 14.4, a statistically significant difference, p = 0.03. For general (non-standard) rates, the relative risk of average suicide in the period was RR = 4.2 times higher for public security professionals compared to the population of the state of Ceará. In relation to the standardized suicide rate, RR = 1.7. The profile of public security suicides was: married 35 (61.4%), middle age 36 (63.2%), men 56 (98.2%), low schooling 36 (63.2%), low income 43 (75.4%), military police 50 (87.7%), low patent 43 (75.4%), operational service 37 (64.8%), firearm as a suicide instrument 42 (73.7% ). For suicide attempts there were n = 173 attempts practiced by 107 professionals. That's because some professionals tried suicide more than once in the period. The association for multiple attempts had significant variables: personality disorder p = 0.01 RR = 2.7, hospitalized in a psychiatric hospital p = 0.01 RR 1.8, addiction p = 0.02 RR 2.0 and depression p = 0.00 RR = 4.3. The association for consumed suicide showed significant: elderly p = 0.00 RR 6.5, low income p = 0.03 RR = 2.5, reserve / retirement p = 0.00 RR = 6.1, firearm p = 0.00 RR 3.9. However, higher education showed to be protective factor p = 0.01 RR = 0.13. It is concluded that public security professionals formed a vulnerable group for suicide during the period studied, that this vulnerability affects public health and public safety, that the risk factors for suicide are similar to those of the world population, except for the state The use of firearms and age. It was suggested that actions to prevent suicide cases should be carried out, such as lectures on the subject, strengthening public health health sectors, monitoring of suicides and attempts with urgent and interlinked notification to the health surveillance sectors of the state and Of the federation.